2019
DOI: 10.1002/jsc.2288
|View full text |Cite|
|
Sign up to set email alerts
|

Use of the pathfinder network scaling to measure online customer reviews: A theme park study

Abstract: We use pathfinder network scaling (PENETS) approach to measure and evaluate theme park visitors' online reviews. PFNETS as an effective tool of big data analytics can be used to identify unobserved meaningful interrelationships between concepts.Although there are many research analyzing online reviews, this study is the first attempt to use an analytical approach of PFNETS to explore online reviews in theme park visitor experiences. The article collects 14,142 effective reviews of the world's first Disneyland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Huang et al, 2017;Nilashi et al, 2015;Sinha et al, 2018), or three (e.g. Basaran et al, 2020;Fronzetti Colladon et al, 2019;Pantano & Dennis, 2019;Ren et al, 2019) Big Data requirements. The examined IT solutions commonly revolve around the potential of Big Data practice considering smart cities or smart destinations (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Huang et al, 2017;Nilashi et al, 2015;Sinha et al, 2018), or three (e.g. Basaran et al, 2020;Fronzetti Colladon et al, 2019;Pantano & Dennis, 2019;Ren et al, 2019) Big Data requirements. The examined IT solutions commonly revolve around the potential of Big Data practice considering smart cities or smart destinations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al, 2018;Önder et al, 2016;Scuderi & Dalle Nogare, 2018;Tingting, 2019), recommendations or reviews (e.g. Fronzetti Colladon et al, 2019;Nilashi et al, 2015;Ren et al, 2019), and predictions or forecasting (e.g. Cheng & Zhao, 2019;Fronzetti Colladon et al, 2019;Pan & Yang, 2017;Song et al, 2013;Tsai, 2014;Yang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media provides an entertainment experience to users, and competence and autonomy directly influenced enjoyment [26]. SNS is known to provide various reviews for theme parks [27]. It is found that Twitter enhanced hard news knowledge when users have a higher need for orientation [25].…”
Section: Sns Usesmentioning
confidence: 99%